(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article are considered questions of economic and legal regulation in the health system, directed on implementation of the major or important social programs in Republic of Kazakhstan in modern period of time. The analysis of governmental activities, their purposes and tasks in the health care system is carrying. Key words: health system, nation health, social protection, health system.